Entrepreneurial Risk Taking and Performance of Small and Medium Scale Enterprises (SMEs) in Kano State, Nigeria - Egele, Amaka Cordelia; Muhammad, Kibuuka; Mutenyo, John (NIU Journal of Social Sciences, 2018)
Risk taking is a dominant attribute of entrepreneurial activities, as the higher the risk-taking orientation, the higher a firmâ€™s profitability and growth. The main purpose of this study was to establish the effect of entrepreneurial risk taking on performance of small and medium scale enterprises (SMEs) in Kano State, Nigeria. Data for the study was obtained through questionnaire and interview from 393 owners, managers and staff of SMEs in Kano state, Nigeria, on a cross sectional research design. Results using Pearson linear correlation and regression analysis have a positive significant relationship between entrepreneurial risk taking and performance of SMEs. Entrepreneurial risk taking has a positive impact on performance of SMEs in Kano State, Nigeria. Entrepreneurial risk taking had a significant effect (F â€“ statistic = 35.959; t â€“ statistic = 5.997) P= 0.001. The study adds value to the growing body of knowledge in the field of entrepreneurial development activities. The study recommends that operators should always identify and assess the trends of the opportunities impending before taking risk not just dare risk, this will help to address the rate at which SMEs managers, owners and staff  take risk, so that risk taking will relate and significantly influence their performance. The study serves as a reference to anyone who is interested in establishing his personal business as it provides insight into the importance of entrepreneurial risk taking in starting a business and also for any organization that is interested in achieving profitability or continue sustaining effective business venture. Key words: entrepreneurial risk taking, small and medium scale enterprises (SMEs), Performance of SMEs.